Exploring Interracial Relationships: Marguerite Duras’ Portrayal of Love Between White Women and Asian Men in The Lover Trilogy - He, Yifan (Transactions on Social Science, Education and Humanities Research, 2024)
In "The Lover Trilogy," Margaret Duras’ autobiographical novels, the discrimination of white people against colored races, the struggle of women in a patriarchal society, and the subtleties of class differences can all be found in the story of a couple of lovers. However, there is no absolute imbalance of power, since a poor white woman is still allowed to "look down" on a rich Asian man. Based on the text of "The Lover Trilogy," the dual perspectives of post-colonialism and feminist theories, and references to corresponding historical backgrounds and the author’s personal life, this paper analyzes the subtle dislocation and balance of social power in both societies through the love affair between a white woman and an Asian man in Duras’ novels. Being rebellious and losing her father at an early age, the white girl is thereby attracted to a Chinese male from a rich family who is much older than her. Although the Chinese lover enjoys advantages in terms of age, social status, and gender, as a white person living in the colony, the young girl has a superior social status. However, this misplaced "balance" cannot contribute to the completion of the love between the white woman and the Asian man. Instead, both the great opposition from society and family and their subliminal values assimilated by society have put the interracial love in an awkward situation that eventually ended with regrets.